2015
DOI: 10.1002/jcb.25139
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Medium Supplementation Regimen for Initiation of Hepatocyte Differentiation in Human Induced Pluripotent Stem Cells

Abstract: Human induced pluripotent stem (hiPS) cells are an ideal source for hepatocytes. Glucose and arginine are necessary for cells to survive. Hepatocytes have galactokinase (GALK), which metabolizes galactose for gluconeogenesis, and ornithine transcarbamylase (OTC), which converts ornithine to arginine in the urea cycle. Hepatocyte selection medium (HSM) lacks both glucose and arginine, but contains galactose and ornithine. Although human primary hepatocytes survive in HSM, all the hiPS cells die in 3 days. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…A previous study demonstrated that the expression levels of GALK1 and GALK2 are increased in iPS cells cultured in HDI that lacks glucose and is supplemented with galactose (14). These data suggest that glucose deprivation and galactose supplementation affect the transcription of GALK1 and GALK2.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…A previous study demonstrated that the expression levels of GALK1 and GALK2 are increased in iPS cells cultured in HDI that lacks glucose and is supplemented with galactose (14). These data suggest that glucose deprivation and galactose supplementation affect the transcription of GALK1 and GALK2.…”
Section: Discussionmentioning
confidence: 71%
“…hepatocyte lineage. One major problem is that iPS cells do not survive in HSM and HDI beyond 3 and 7 days, respectively (14). To overcome this limitation, the present study used 3BP and/or 2DG treatment to investigate an alternative to glucose deprivation and galactose supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to the incubation time of 7 days, which was relatively short for hepatocyte differentiation. Another reason might be that additional growth factors or small molecules were necessary [Tomizawa et al, ]. In future analyses, we plan to conduct investigations with longer incubation after transfection and addition of growth factors and small molecules to WE.…”
Section: Discussionmentioning
confidence: 99%